The 24-Form Tai Chi Improves Anxiety and Depression and Upregulates miR-17-92 in Coronary Heart Disease Patients After Percutaneous Coronary Intervention - Liu, Jia; Yu, Ping; Lv, Wei; Wang, Xinxin (Frontiers in Physiology, 2020)
Background: Anxiety and depression are common symptoms in the patients with coronary heart disease (CHD) after percutaneous coronary intervention (PCI). The 24-form Tai Chi may exert protective function for CHD patients after PCI by improving anxiety and depression. Methods: Patients who received PCI after 1-4 days were randomly assigned to the 24-form Tai Chi group (TG) and the control group (CG). The differences in anxiety, depression, Medical Outcomes Study 36‐item Short‐Form Health Survey (SF-36) before and after an average of 10 months of Tai Chi intervention were compared in the both groups to analyze the effects of Tai Chi on the emotion and life quality of CHD patients. Meanwhile, the relative levels of miR-17-92 were measured by using real-time qPCR. The association between the relative levels of miR-17-92 and anxiety and depression of CHD patients after PCI was analyzed. Adjusted Cox models were used to explore the effect of Tai Chi exercise in CHD patients. Results: After 10 months of intervention, the changes in the anxiety subscale (P = 0.002), the depression subscale (P = 0.008), and in the stress (P = 0.015) scores were higher in the TG group when compared to the CG group. The proportion of anxious (P = 0.045) and depressed subjects (P = 0.042) in the TG group was lower than that in the CG group. On the other hand, On the other hand, the increase in SF-36 scores and in relative levels of miR-17-92 was significantly higher in the TG group when compared with the CG group (P < 0.05). Serum level of miR-17-92 had a negative correlation with anxiety, depression and stress scores (P < 0.01). Conclusions: The 24-form Tai Chi improved anxiety and depression, and upregulated miR-17-92 levels in CHD patients after PCI.